Recognizing the Urban Image Elements of Tbilisi Based on the Description of Tourists During the Qajar era - Mehdi Nilipour; Ahad Nejad Ebrahimi (توسعه پایدار شهری)
Tbilisi is one of the historic cities whose image has always been of interest to tourists and travel writers. Many foreign tourists during the Qajar period, on their journeys, cited Tiflis and presented their descriptions of the city in their travelogues. The purpose of this research is to determine the components of Tbilisi's urban image during the Qajar period from the perspective of historical travelogues. In this research, by studying eleven travelogues written by domestic and foreign tourists during the Qajar era and referring to the city of Tbilisi, categories and subcategories that include symbols and symbol bearers were extracted using the qualitative content analysis method. After that, the position of each of the symbols and symbol bearers in the city of Tbilisi has been determined, and finally, the map of the city of Tbilisi has been drawn. The categories included path, edge, landmark, district, and node. The results showed that there were long and convenient paths in the Russian district and the European part, as well as near the bridges. Also, the river Kura played the role of the edge in the city's image, and the city had four districts: Russian, Yerevan, German, and Georgian. The nodes included traffic and activity nodes. Traffic nodes included the bridges on the river and the intersections of the main roads, and activity nodes included the Mushthaid Garden, the Garden of Europe, Alexander Garden, the Square, and the Bazaar. Finally, the city had landmarks such as mountains, ruined towers, Narin Qala, The White Shrine of Sheikh San'an, churches, and mosques.